Switzerland : 2006 Article IV Consultation; Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Switzerland. (IMF Staff Country Reports; Country Report, 2006)
Switzerland showed commendable economic growth with low inflation and increasing employment. Executive Directors commended the prudent macroeconomic management, sound monetary and fiscal policy frameworks, structural reforms, and flexible labor markets. They noted that the monetary policy framework continues to serve Switzerland well, underpinned by effective practices of the Swiss National Bank (SNB). They agreed that the Swiss financial system appears to be healthy and dynamic, and appreciated the regulatory and supervisory framework, and the vigilance in monitoring financial sector risks.